PENGARUH INOVASI PRODUK, HARGA, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN SEPEDA MOTOR VESPA - Dwi Putra, Made Caesar Surya; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
This study aimed to describe the influence of product innovation, price, brand image and service quality on customer loyalty in the city of Denpasar. Samples are 102 respondents using purposive sampling. Collecting data in this study using questionnaires and interviews. The analysis technique used in this research is multiple linear regression analysis. Based on the analysis found that product innovation has a positive and significant impact on customer loyalty vespa motorcycle in the city of Denpasar. Price has a positive and significant impact on customer loyalty vespa motorcycle in the city of Denpasar. Brand image has a positive and significant impact on customer loyalty vespa motorcycle in the city of Denpasar. Quality of service has a positive and significant impact on customer loyalty vespa motorcycle in the city of Denpasar. It proves that innovation of product, price, brand image and quality of service can increase customer loyalty Vespa motorcycle in the city of Denpasar.
Keywords: product innovation; price; brand image, service quality; customer loyalty